Comments to: Risk factors for late defecation and its association with the outcomes of critically ill patients: a retrospective observational study. Issue 1 (December 2016) - Prat, Dominique; Sztrymf, Benjamin
Abstract In a previous retrospective work, it has been postulated that early enteral nutrition was a protective factor against late defecation and its subsequent consequences in critically ill patients. We raise concerns about methodological issues limiting the conclusions.